Makna Mabebasan Geguritan Bima Suarga Dalam Perspektif Panca Sradha - Subrata, I Nyoman; Sudarma, I Putu; Toya Wisuda, Pande Putu (Jayapangus Press, 2024)
Entering the current era of digitalization, the Balinese Hindu community still adheres to local wisdom values, including the moral, social, philosophy (tatwa) and religious values ​​contained in geguritan (religious song) Bima Suarga. This research aims to examine the meaning of Geguritan Bima Suarga in Panca Sradha perspective. Research data was obtained through document study by analyzing the Geguritan Bima Suarga text, observations and interviews with members of the group (sekaa) santhi “Gangga Lingga Suara